Phenoxodiol, an anticancer isoflavene, induces immunomodulatory effects in vitro and in vivo - Georgaki, S.; Skopeliti, M.; Tsiatas, M.; Nicolaou, K.A.; Ioannou, K.; Husband, A.; Bamias, A.; Dimopoulos, M.A.; Constantinou, A.I.; Tsitsilonis, O.E. (Journal of Cellular and Molecular Medicine, 2009)
Phenoxodiol (PXD) is a synthetic analogue of the plant isoflavone genistein with improved anticancer efficacy. Various properties and mechanisms of action have been attributed to the drug, the most important being its ability to sensitize resistant tumour cells to chemotherapy, which led to its fast track FDA approval for phase II/III clinical trials. In this study, we examined the effects of PXD on human peripheral blood mononuclear cells (PBMC) and its potential role in regulating immune responses. We show that PXD, at concentrations ≥1 μg/ml (4 μM), inhibited proliferation and reduced the viability of healthy donor-derived PBMC. In contrast, lower PXD concentrations (0.05-0.5 μg/ml) augmented, upon 3-day incubation, PBMC cytotoxicity. Experiments with purified CD56 + lymphocytes revealed that PXD enhanced the lytic function of natural killer (NK) cells by directly stimulating this lymphocytic subpopulation. Furthermore, in an in vivo colon cancer model, Balb/C mice administered low-dose PXD, exhibited significantly reduced tumour growth rates and prolonged survival (in 40% of the animals). Ex vivo results showed that PXD stimulated both NK and tumour-specific cell lytic activity. We conclude that PXD, when administered at low concentrations, can act as an immunomodulator, enhancing impaired immune responses, often seen in cancer-bearing individuals. © 2009 The Authors Journal compilation © 2009 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
Keywords: Anticancer drug; Immune responses; In vivo model; Isoflavones; NK cytotoxicity; Phenoxodiol